Proceedings. International Symposium on Advanced Packaging Materials: Processes, Properties and Interfaces, 2005.
DOI: 10.1109/isapm.2005.1432084
|View full text |Cite
|
Sign up to set email alerts
|

Design, fabrication, and reliability assessment of embedded resistors and capacitors on multilayered organic substrates

Abstract: Embedded passives provide a practical solution to microelectronics miniaturization. In a typical circuit, over 80 percent of the electronic components are passives such as resistors, inductors, and capacitors that could take up to 50 percent of the entire printed circuit board area. By integrating passive components within the substrate, embedded passives reduce the system real estate, eliminate the need for discrete components and assembly of same, enhance electrical performance and reliability, and potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…It was observed that after 1,000 h of reliability testing at 85°C and 85% RH, the capacitance increased by about 4% [17]. In another work, capacitance was found to increase by about 10% after 4 h of pressure cooker testing (121°C and 100% RH) [18].…”
Section: Introductionmentioning
confidence: 90%
“…It was observed that after 1,000 h of reliability testing at 85°C and 85% RH, the capacitance increased by about 4% [17]. In another work, capacitance was found to increase by about 10% after 4 h of pressure cooker testing (121°C and 100% RH) [18].…”
Section: Introductionmentioning
confidence: 90%
“…The reliability of embedded capacitors with polymerceramic composite dielectric under elevated temperature and humidity conditions (85 • C and 85% RH) has been investigated [22]. After 100 h of elevated temperature and humidity tests, the capacitance was found to increase by about 4%.…”
Section: Reliability Of Embedded Capacitors Under Temperature Humentioning
confidence: 99%
“…The board is fully cured at 150 C for 1 h to complete the capacitor process. Once the capacitor layer is completed, resistor layer is fabricated using a screen print lift-off process followed by the electroplated microvia process to complete the TV2 fabrication [11].…”
Section: A Test Vehicle Fabrication Detailsmentioning
confidence: 99%